2017
DOI: 10.1007/s00701-017-3266-1
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary management of clival chordomas; long-term clinical outcome in a single-institution consecutive series

Abstract: ObjectiveChordomas of the skull base have high recurrence rates even after radical resection and adjuvant radiotherapy. We evaluate the long-term clinical outcome using multidisciplinary management in the treatment of clival chordomas.MethodsBetween 1984 and 2015, 22 patients diagnosed with an intracranial chordoma were treated at the Karolinska University Hospital, Stockholm, Sweden. Sixteen of 22 were treated with Gamma Knife radiosurgery (GKRS) for tumour residual or progression during the disease course. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 62 publications
4
24
0
Order By: Relevance
“…Most recently, Förander et al demonstrated the role of GKSRS in the management of residual disease after no previous radiation and management of progression after previous SRS. 11 With dosing parameters similar to that in our study, a tumor control rate of 50% at 15 years for first time GKSRS patients was noted in the setting of an ARE rate of 18%; notably, a majority of the recurrences were considered out of field. In the repeat SRS subcohort of six patients, a prominent effect on tumor control was also noted.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Most recently, Förander et al demonstrated the role of GKSRS in the management of residual disease after no previous radiation and management of progression after previous SRS. 11 With dosing parameters similar to that in our study, a tumor control rate of 50% at 15 years for first time GKSRS patients was noted in the setting of an ARE rate of 18%; notably, a majority of the recurrences were considered out of field. In the repeat SRS subcohort of six patients, a prominent effect on tumor control was also noted.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, location of the treated recurrence relative to the prior radiation field did not limit delivery of an effective and safe radiation dose, with median maximum and marginal doses of 28 and 15 Gy, respectively; these dosing schemes are similar to those reported by other GKSRS series in the literature. [10][11][12][13][14][15] As discussed in the following, it is likely that the judicious use of surgery helped radiation outcomes for patients with infield/ marginal recurrences adjacent to the brainstem. The largest radiosurgery series to date reported outcomes for 71 patients, 20 of whom were treated for recurrence following prior radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Treating chordomas can be challenging due to their proximity to various vital structures and their high recurrence rate, therefore, en bloc resection may not be possible, and microsurgery with the aim of gross total resection or subtotal resection followed by adjuvant therapy such as radiotherapy is considered to be the treatment of choice. 1,2,4 Most chordoma patients treated with the transsphenoidal approach. 8 However, more extensive tumors treated with the transbasal or transpetrosal approach.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, more extensive tumors treated with the transbasal or transpetrosal approach. 2 Other approaches include trans mandibular, transcochlear, transcondylar, subtemporal-preauricular, and extreme lateral. 1 Chordomas are often resistant to conventional radiotherapy.…”
Section: Discussionmentioning
confidence: 99%